Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Metode AHP (Studi Kasus: PT WMTI) - Ali, Ficky Septian; Purnomo, Agus Sidiq (Jurnal Sains dan Teknologi (JSIT), 2022)
The implementation of Lean Startup and Product Management in a startup is very much needed to survive in a sustainable manner. PT Web Media Technology Indonesia (PT WMTI) has implemented Lean Startup and Product Management and has encouraged all its employees to implement Lean Startup at work. The best PT WMTI employees in implementing Lean Startup were analyzed using the Decision Support System (DSS) with Analytical Hierarchical Process (AHP) method. DSS can provide recommendations for the best employees based on ranking. Of the 8 employees, there are 3 employees with the largest ranking, namely: A01 = 0,192 ; A04 = 0,155 ; and A03 = 0,117. Based on the results of the consistency test, the resulting CR (Consistency Ratio) value of 0.08174 which means the error value is below 10% so that the consistency index value and the results of the assessment are correct, consistent, and can be used. The results of the study indicate that the implementation of Lean Startup and Product Management at Niagahoster is quite good because of the socialization and ongoing programs.